2010
DOI: 10.1038/aja.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Significance of age and comorbidity as prognostic indicators for patients with bladder cancer

Abstract: The aim of this study was to determine the impact that age and comorbidity status have on both overall and bladder cancer-specific survival of bladder cancer patients. We obtained medical information pertaining to a population of 528 patients with newly diagnosed bladder cancer from Chung-Ang University Hospital cancer registry. The Adult Comorbidity Evaluation-27 (ACE-27) test, which has been previously validated in adult cancer patients, was used to assess comorbidity. We evaluated differences in the demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…This population has been associated with many comorbidities and a shorter life expectancy [ 2 10 ]. Comorbiditity and age have been found to be independent predictors of overall survival (OS) in BC patients [ 12 13 14 ].…”
Section: Defining Elderly Patients and Life Expectancymentioning
confidence: 99%
See 2 more Smart Citations
“…This population has been associated with many comorbidities and a shorter life expectancy [ 2 10 ]. Comorbiditity and age have been found to be independent predictors of overall survival (OS) in BC patients [ 12 13 14 ].…”
Section: Defining Elderly Patients and Life Expectancymentioning
confidence: 99%
“…When selecting patients to undergo RadC, the institution and urologist (training and experience) are important in the outcome of the procedure [ 21 ]. Elderly patients undergo RadC for MIBC less often than younger patients [ 9 13 22 23 ]. Specifically using the SEER-Medicare data, two separate studies showed that older patients (age >80 [ 24 ], >75 [ 25 ]) are less likely treated with RadC.…”
Section: Elderly Population Undergoing Bladder Cancer Treatments (Radmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, while advances in medicine have increased the mean lifespan of the population, it has also generated a society of elderly patients affected by this disease and likely to seek treatment. Older patients have more years to compound comorbidities and it has previously been shown that comorbidity is an important predictor of overall survival (OAS) in patients with BC, including those treated with cystectomy [4–6]. Other studies have also shown a higher stage at diagnosis, higher rate of upstaging on final pathology and a longer delay to definitive therapy for older patients [7–10].…”
Section: Introductionmentioning
confidence: 99%
“…When F-actin expression is increased, F-actin aligns with the cell's polarity, which results in reduced tumour metastasis. [34][35][36] Increases in the density of F-actin result in loose arrangements that are not aligned with cell polarity and result in increased tumour metastasis. Therefore, delta Np63 may be a new drug target for TCCB therapy, especially in efforts to target invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%